Trypanosomatid Infections: How Do Parasites and Their Excreted–Secreted Factors Modulate the Inducible Metabolism of l-Arginine in Macrophages? - Holzmuller, Philippe; Geiger, Anne; Nzoumbou-Boko, Romaric; Pissarra, Joana; Hamrouni, Sarra; Rodrigues, Valérie; Dauchy, Frédéric-Antoine; Lemesre, Jean-Loup; Vincendeau, Philippe; Bras-Gonçalves, Rachel (Frontiers in Immunology, 2018)
Mononuclear phagocytes (monocytes, dendritic cells, macrophages) are among the first host cells to face intra- and extracellular protozoan parasites such as trypanosomatids, and significant expansion of macrophages has been observed in infected hosts. They play essential roles in the outcome of infections caused by trypanosomatids, as they can exert a powerful antimicrobial activity, but also promote parasite proliferation. These varied functions, linked to their phenotypic and metabolic plasticity, are exerted via distinct activation states, in which L-arginine metabolism plays a pivotal role. Depending on the environmental factors and immune response elements, L-arginine metabolites contribute to parasite elimination, mainly through nitric oxide (NO) synthesis, or to parasite proliferation, through L-ornithine and polyamine production. To survive and adapt to their hosts, parasites like trypanosomatids developed mechanisms of interaction to modulate macrophage activation in their favor, by manipulating several cellular metabolic pathways. Recent reports emphasize that some excreted/secreted (ES) molecules from parasites and sugar-binding host receptors play a major role in this dialogue, particularly in the modulation of the macrophage’s inducible L-arginine metabolism. Preventing L-arginine dysregulation by drugs or by immunization against trypanosomatid ES molecules or by blocking partner host molecules may control early infection, and is a promising way to tackle neglected diseases including Chagas disease, leishmaniases and African trypanosomiases. The present review summarizes recent knowledge on trypanosomatids and their ES factors with regard to their influence on macrophage activation pathways, mainly the NO synthase/arginase balance. The review ends with prospects for the use of biological knowledge to develop new strategies of interference in the infectious processes used by trypanosomatids, in particular for the development of vaccines or immunotherapeutic approaches.